Regulating the activity of boronate moiety to construct fluorescent probes for the detection of ONOO−in vitro and in vivo. Issue 48 (5th December 2022) - Ji, Xin; Zhou, Junliang; Liu, Chang; Zhang, Jian; Dong, Xiaochun; Zhang, Fuli; Zhao, Weili
Abstract : Abnormal intracellular peroxynitrite (ONOO − ) concentration is related to oxidative damage, which is correlated with many pathological consequences. Abstract : Abnormal intracellular peroxynitrite (ONOO − ) concentration is related to oxidative damage, which is correlated with many pathological consequences, such as local inflammation and other diseases. In this work, a series of resorufin benzyl ether-based fluorescent probes were designed using boronate as a recognizing moiety installed on a phenyl moiety for ONOO − detection via a self-immolation mechanism. The location of the boronate as well as the substitution patterns on the phenyl moiety were investigated and the responding behaviors of the designed probes to ONOO −, other reactive oxygen species, and biothiols were examined. It was found that all the immolative probes were inevitably dominated by ONOO − . Compared with other probes, p -Borate possessed favorable selectivity and high sensitivity to ONOO − . Moreover, p -Borate was successfully used to detect ONOO − in cells and inflamed mice.